2020
DOI: 10.1108/jbim-04-2020-0183
|View full text |Cite
|
Sign up to set email alerts
|

Linking supplier selection and management strategies with mass customization capability

Abstract: Purpose Owing to the paucity of literature, in the specific context of mass customization (MC), that explains what factors need to be considered while selecting suppliers and what strategies need to be implemented for effective management of suppliers, this paper aims to explore the effective supplier selection and management strategies and also investigate their impact on the development of mass customization capability (MCC). Design/methodology/approach Through an extensive review of literature, a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 86 publications
(100 reference statements)
1
13
0
Order By: Relevance
“…To answer our first research question we have looked at the corporate values and employee’s behavior (Homburg et al , 2003; Gebauer et al , 2010b; Pereira et al , 2018; Fliess and Lexutt, 2019; Dang et al , 2019; Jovanovic et al , 2019), when applying a customization strategy (Sousa and Da Silveira, 2019; Ullah and Narain, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer our first research question we have looked at the corporate values and employee’s behavior (Homburg et al , 2003; Gebauer et al , 2010b; Pereira et al , 2018; Fliess and Lexutt, 2019; Dang et al , 2019; Jovanovic et al , 2019), when applying a customization strategy (Sousa and Da Silveira, 2019; Ullah and Narain, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In today’s highly competitive markets, one of the ways to gain differentiation from competitors is by offering value-added services (Homburg et al , 2003). For doing so, many organizations from different industries across the world have embraced customization strategies (Ullah and Narain, 2020) to meet customer demands for a unique and tailored offering (Da Silveira et al , 2001; Duray et al , 2000; Neu and Brown, 2005; Homburg et al , 2003; Matthyssens and Vandenbempt, 1998) which implies that manufacturers must build close relationships with customers to obtain knowledge about customer requirements and changes promoting the implementation of successful service strategies (Fliess and Lexutt, 2019; Martinez et al , 2010; Sousa and Da Silveira, 2019; Baines et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…By using appropriate ICTs, mass customizer can identify, select and compare suppliers to develop a base of capable suppliers that renders both sourcing and supplier flexibility. Besides, mass customizers can better integrate with flexible suppliers which could lead to the achievement of enhanced organizational performance through increased information transparency, joint problem solving and co-creation of unique values (Ullah and Narain, 2021c). Thus, the impact of both sourcing and supplier flexibility on MCC is higher when the organizations use appropriate ICTs.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, organizations are striving to achieve flexibility in various aspects of business to effectively respond to the environmental uncertainties and to satisfy the idiosyncratic needs of customers (Ullah and Narain, 2021a; Mishra and Mishra, 2019). While seeking flexibility to fulfill the requirements of MC, extant literature emphasizes looking beyond the internal operational effectiveness and establishing means for responsive sourcing and supply for value creation (Liao et al , 2010; Sinkovics et al , 2018; Ullah and Narain, 2021c). The studies have shown that flexibility associated with supply chain offers a collaborative competence that allows the focal firms to plan appropriate responses for current and future state of affairs by selecting, reconfiguring, monitoring and managing the suppliers (Huo et al , 2018; Ullah and Narain, 2021c).…”
Section: Introductionmentioning
confidence: 99%
“…The devotion of top management is regarded as critical to achieving the organizational objectives. Top management makes strategic decisions, and the outcomes of those decisions have an impact on the success of the business [38]. Managers hold the responsibility of deciding how the resources will be utilized, what strategies needs to be followed and what changes need to be implemented.…”
Section: Top Management Commitmentmentioning
confidence: 99%